ACCURACY OF SELF-REPORT OF ON-ROAD CRASHES AND TRAFFIC OFFENCES IN A COHORT OF YOUNG DRIVERS: THE DRIVE STUDY. (7th October 2012) - Boufous, S; Ivers, R; Senserrick, T; Stevenson, M; Norton, R; Williamson, A
Abstract : Background: Road traffic injuries are a leading cause of death and disability worldwide, particularly among young adults. While surveys are widely used to measure the incidence of on-road crashes and offences, little is known about the validity of self-reports of these events, particularly among young drivers. Aims/Objectives/Purpose: To examine the accuracy of self-report of on-road crashes and traffic offences among participants in the DRIVE study: a cohort study of 20 822 drivers, aged 17–24-year-old, recently licensed in New South Wales, Australia. Methods: A total of 2991 DRIVE study participants who completed the follow-up questionnaire, approximately 2 years after joining the study, were asked whether they had been involved in an on-road crash or were convicted for a traffic offence during the year prior to the survey. This information was subsequently linked to police recorded crash and offence data to determine the level of accuracy of these self-reports. Results/Outcomes: Young drivers reported more crashes and traffic offences than those recorded in the police database during the 1 year study period. The findings showed a high level of accuracy in young drivers' self-report of police recorded crashes (85.1%; 95% CI 78.2% to 92.1%) and of police recorded traffic offences (83.0%; 95% CI 79.4% to 86.6%). Significance/Contribution to the Field: The results suggest that surveys may be useful tools for estimating the incidence of traffic crashes and offences in young drivers. The findings are particularly relevant to countries and jurisdictions where access to administrative data is limited.